Mesosphaerum suaveolens (Lamiacae): Source of antimicrobial and antioxidant compounds (Research, Society and Development, 2020)
The use in folk medicine of leaves of Mesosphaerum suaveolens for the treatment of diseases of the digestive system and respiratory system, raised the hypothesis that its volatile oil has biological properties against pathogenic microorganisms. To evaluate this hypothesis, the antibacterial, antifungal activity against Candida yeast strains, which modifies the action of antibiotics and antioxidants (DPPH) was evaluated in vitro. In addition, it was determined by means of Gas Chromatography (GC-FID), the constituents present in the essential oil. The results show that M. suaveolens oil has antibacterial activity against standard and multidrug-resistant strains of Staphylococcus aureus, with a MIC of 64 and 256 μg/mL respectively, however it does not have the capacity to enhance the action of commercial antibacterials. Regarding the anti-Candida activity, it was possible to observe that there was biological action, since they presented IC50 de 18.15 µg/mL for Candida albicans URM and 40.4 for Candida tropicalis INCQS 40042. In addition, the oil was able to modulate fluconazole for all strains analyzed. As for the antioxidant action, the oil demonstrated that even in low percentages, there is an action in the reduction of free radicals (IC50> 200 µg/mL). Such activities may be related to the major constituent of the oil, the sesquiterpene β-caryophyllene (C17H28O2). Thus, M. suaveolens oil is a natural source with antimicrobial and antioxidant properties.